Incidental discovery of xanthogranulomatous cholecystitis as a mimicker of gall bladder adenocarcinoma: A retrospective cohort study. - Imam, Zeenat Sarmadi; Rabab, Shadan; Bharti, Kumari Sunita; Langhe, Makarand Hemant; Kumar, Bipin; Mandal, Manish; Singh, Rakesh Kumar (Student’s Journal of Health Research Africa, 2025)
Background Xanthogranulomatous cholecystitis (XGC) is an inflammatory condition characterised by the intramural accumulation of lipid-laden macrophages in the bladder wall. Sometimes, XGC results in adhesions of the gall bladder to adjacent organs, causing the formation of fistulous tracts and bladder perforation. Intense adhesions lead to mass formation, giving a false impression of malignancy on radiological investigations and intraoperatively. Such cases are resolved only after final histopathological diagnosis, making it the gold standard. Aims and Objectives: The study was conducted to outline and review the presentations and investigations in cases of XGC in order to structure an approach to managing diagnostic dilemmas in treating such patients. Materials and methods An observational, retrospective study was conducted in the Pathology department at IGIMS, Patna. A total of 1260 cholecystectomy samples with a preoperative diagnosis of gall bladder cancer (GBC), received from January 2019 to December 2024, were included in our study. Cases were selected as per the inclusion and exclusion criteria. Results Statistical analysis showed that out of 1260 specimens, preoperatively diagnosed as GBC, 59 were diagnosed as XGC on histopathological examination (Group X). Group Y had a greater incidence of anorexia and weight loss. Radiological findings on retrospect in group X displayed specific features suggestive of XGC, namely diffuse gall bladder wall thickening, hypoattenuated submucosal nodules, intrahepatic duct dilatation, continuous mucosal line enhancement, and loss of interface between the gall bladder and liver. Conclusion It is difficult to diagnose XGC from GBC preoperatively in all cases. Histopathological examination serves as the cornerstone in such diagnostic dilemmas. Recommendations A multidisciplinary approach and increased awareness are key to accurate diagnosis and appropriate management.